Accelerating the Development of Arabica Coffee Production and Processing to Encourage Business and Economic Improvement of the Kintamani Bali Community: Development of Arabica Coffee Production and Processing of the Kintamani Bali Community - Suriati, Luh; Suwitra, I Made; Astuti, Partiwi Dwi; Udayana, I Gusti Bagus; Selamet, I Ketut; Rustini, Ni Made; Chindrawati, Anak Agung Sagung Manik; Damayanti, Ni Luh Putu Sulis Dewi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study focuses on accelerating the development of Arabica coffee production and processing in Kintamani, Bali, to enhance local business and economic growth. Kintamani, renowned for its distinctive Arabica coffee, faces challenges in productivity, post-harvest processing, and global market access. The program employed a combination of face-to-face methods, counseling, training, and hands-on practices to improve cultivation techniques, post-harvest methods, marketing strategies, and collaboration networks. The method involved direct practice guided by experts, with training on sustainable agricultural practices, modern post-harvest processing technologies, and effective marketing strategies. Results show a significant increase in participants' knowledge, with an understanding of marketing strategies improving from 21.05% to 84.21%, and awareness of product certification rising from 10.53% to 84.21%. These outcomes demonstrate the program's effectiveness in empowering local communities and fostering sustainable development. Recommendations include leveraging social media, certification systems, and stakeholder collaborations to enhance market access and ensure business continuity. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 2: Zero hungerSDG 9: Industry, Innovation, and Infrastructure SDG 12: Responsible Consumption and ProductionSDG 13: Industry, Innovation, and InfrastructureSDG 17: Partnerships for the Goals